A Bibliometric Analysis of Mobile Assisted Second Language Learning - Feng, Juan; Chen, Yong (International Journal of Interactive Mobile Technologies (iJIM), 2022)
This article reviews mobile assisted second language learning (MASLL) with a bibliometric method. The authors collected data of papers related to MASLL from Web of Science and then analyzed the sources, authors, papers, and conceptual structure. The result suggests that: the effects of technology on learning, vocabulary, personalized learning, learning environment, learner attitudes were popular topics in this field; the attention on themes related to “technology” is fading away and the focus of MASLL research is shifting to themes related to “students”. Most-cited journals, authors, and papers are also presented in this article.